RELIGIOUS VALUE IN THE TRAINING MATERIALS OF THE RAMPAK BEDUG DANCE AT SANGGAR HARUM SARI - Tryas Putri, Novia; Setiawati, Rahmida; Hussain, Sajjad (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2022)
This study aims to describe the religious value of the Rampak Bedug Dance as a training material in the Sanggar Fragrant Sari. The object of this research is Rampak Bedug Dance. This research is focused on problems related to Religious Values in Rampak Bedug Dance. This study uses a descriptive research methodology through a qualitative approach. The subjects of this study were the manager of the Harum Sari studio, trainees and musicians. The data collection technique used is triangulation of data derived from observations, interviews, documentation and literature studies. The description of this research discusses dance movements, dance accompaniment, fashion, dance properties, and floor patterns. From the data that has been obtained, interpreted according to Koentjaraningrat's theory into 5 discussions, namely 1) religious emotions, 2) belief systems, 3) rites and ceremonies system, 4) rites and ceremonies equipment, 5) religious people. Based on the data obtained, it is concluded that the Rampak Bedug dance in Sanggar Harum Sari contains religious values which refer to the 5 religious components of Koentjaraningrat. The existence of religious values in the Rampak Bedug Dance is also based on the background of Pandeglang Regency which is part of the Banten province area which was formerly an Islamic kingdom on the island of Java. It can be concluded that the Rampak Bedug dance in Sanggar Harum Sari contains religious values which refer to the 5 religious components of Koentjaraningrat. The existence of religious values in the Rampak Bedug Dance is also based on the background of Pandeglang Regency which is part of the Banten province area which was formerly an Islamic kingdom on the island of Java. It can be concluded that the Rampak Bedug dance in Sanggar Harum Sari contains religious values which refer to the 5 religious components of Koentjaraningrat. The existence of religious values in the Rampak Bedug Dance is also based on the background of Pandeglang Regency which is part of the Banten province area which was formerly an Islamic kingdom on the island of Java.